Large eddy simulations of the Arctic boundary layer around the MOSAiC drift track ... : Large-Eddy-Simulationen der arktischen Grenzschicht um die MOSAiC-Driftroute ... - Littmann, Daniela-Christin (Universität Potsdam, 2024)
The icosahedral non-hydrostatic large eddy model (ICON-LEM) was applied around the drift track of the Multidisciplinary Observatory Study of the Arctic (MOSAiC) in 2019 and 2020. The model was set up with horizontal grid-scales between 100m and 800m on areas with radii of 17.5km and 140 km. At its lateral boundaries, the model was driven by analysis data from the German Weather Service (DWD), downscaled by ICON in limited area mode (ICON-LAM) with horizontal grid-scale of 3 km. The aim of this thesis was the investigation of the atmospheric boundary layer near the surface in the central Arctic during polar winter with a high-resolution mesoscale model. The default settings in ICON-LEM prevent the model from representing the exchange processes in the Arctic boundary layer in accordance to the MOSAiC observations. The implemented sea-ice scheme in ICON does not include a snow layer on sea-ice, which causes a too slow response of the sea-ice surface temperature to atmospheric changes. To allow the sea-ice ... : Das icosahedral non-hydrostatische large eddy model (ICON-LEM) wurde entlang des Driftweges des Multidisciplinary Observatory Study of the Arctic (MOSAiC) in 2019 und 20 angewendet. Das Modell nutzte horizontale Gitterauflösungen zwischen 100m und 800m auf Gebieten mit Durchmessern von 17.5km und 140 km. An den seitlichen Rändern wurde das Modell mit Analysedaten des Deutschen Wetterdienstes (DWD) angetrieben, welche mit ICON im limited area mode (ICON-LAM) mit einer horizontalen Auflösung von 3km herunterskaliert wurden. Ziel dieser Arbeit war es, die flache atmosphärische Grenzschicht in der zentralen Arktis während des polaren Winters mit einem hochauflösenden mesoskaligen Modell zu untersuchen. Die standardmäßigen Einstellungen in ICON-LEM machen es dem Modell unmöglich, die wechselwirkenden Austauschprozesse in der arktischen Grenzschicht gemäß der MOSAiC Beobachtungen abzubilden. Das implementierte Meereis-Schema in ICON beinhaltet keine Schneeschicht auf dem Meereis, was eine zu große Verzögerung der ...